Living with Uncertainty New directions in pastoral development in Africa - Ellis, Jim (2008)
The last few years have seen a major rethinking of some of the hallowed assumptions of range ecology and range management practice. This book examines the management of policy implications of this new ecological thinking for pastoral development in dryland areas. With examples drawn from all over Africa, the contributors examine the consequences of living with uncertainty for pastoral development planning, range and fodder management, drought responses, livestock marketing, resource tenure, institutional development and pastoral administration.